The capacity of hydrous fluids to transport and fractionate incompatible elements and metals within the Earth's mantle. (5th June 2014) - Adam, John; Locmelis, Marek; Afonso, Juan Carlos; Rushmer, Tracy; Fiorentini, Marco L.
Abstract Both silicate melts and aqueous fluids are thought to play critical roles in the chemical differentiation of the Earth's crust and mantle. Yet their relative effects are poorly constrained. We have addressed this issue by measuring partition coefficients for 50 trace and minor elements in experimentally produced aqueous fluids, coexisting basanite melts, and peridotite minerals. The experiments were conducted at 1.0–4.0 GPa and 950–1200°C in single capsules containing (either 40 or 50 wt %) H2O and trace element‐enriched basanite glass. This allowed run products to be easily identified and analyzed by a combination of electron microprobe and LAM‐ICP‐MS. Fluid and melt compositions were reconstructed from mass balances and published solubility data for H2O in silicate melts. Relative to the basanite melt, the solutes from H2O‐fluids are enriched in SiO2, alkalis, Ba, and Pb, but depleted in FeO, MgO, CaO, and REE. With increasing pressure, the mutual solubility of fluids and melts increases rapidly with complete miscibility between H2O and basanitic melts occurring between 3.0 and 4.0 GPa at 1100°C. Although LREE are favored over HREE in the fluid phase, they are less soluble than the HFSE (Nb, Ta, Zr, Hf, and Ti). Thus, the relative depletions of HFSE that are characteristic of arc magmas must be due to a residual phase that concentrates HFSE (e.g., rutile). Otherwise, H2O‐fluids have the capacity to impart many of the geochemical characteristics that distinguish some rocks and melts from the deep mantle lithosphere (e.g., MARID and lamproites).